Stroke in young adults: A 3-month outcome analysis and predictors of mortality in Northeast India – A regional perspective - Baiakmenlang Synmon,; Iada Rilang Tiewsoh,; Tamajyoti Ghosh,; SR Sharma,; C Daniella,; Nasheman Khongthaw,; Pynjanai Thongni, (Asian Journal of Medical Sciences, 2025)
Background: Stroke in young adults (18–50 years) is a growing public health challenge, with Northeast India reports a disproportionately high incidence (36.7% of total strokes). This study analyzes functional outcomes and mortality predictors using the modified Rankin scale in young stroke patients.Aims and Objectives: To study the various stroke subtypes among young adults from this country region. Second, to study the outcome of stroke at the 28th and 30th day, and further analyze the predictors of mortality.Materials and Methods: A prospective cohort of 128 young stroke patients (ischemic, hemorrhagic, and venous thrombosis) was assessed at discharge and 3-month follow-up. Regression analysis identified predictors of mortality and poor outcomes.Results: Out of 348 stroke cases, 128 (36.7%) were young patients (aged 18–55). Ischemic stroke was most common (49.2%), followed by intracerebral hemorrhage (45.3%), subarachnoid hemorrhage (3.9%), and cerebral venous thrombosis (1.6%). The study observed a total of 22 patient deaths (5.8% mortality rate). The timing of these deaths was as follows: eight patients died at discharge, nine patients passed away within the first 28 days, and five patients died by the end of three months.Conclusion: Targeted interventions addressing stroke severity, subtype, and complications are critical to improving outcomes in young adults.